Cryopreservation of testicular and epididymal sperm: techniques and clinical outcomes of assisted conception (Clinics, 2013)
The introduction of the technique of intracytoplasmic sperm injection to achieve fertilization, especially using surgically retrieved testicular or epididymal sperm from men with obstructive or non-obstructive azoospermia, has revolutionized the field of assisted reproduction. The techniques for the retrieval of spermatozoa vary from relatively simple percutaneous sperm aspiration to open excision (testicular biopsy) and the more invasive Micro-TESE. The probability of retrieving spermatozoa can be as high as 100% in men with obstructive azoospermia (congenital bilateral absence of the vas deferens, status post-vasectomy). However, in nonobstructive azoospermia, successful sperm retrieval has been reported in 10-100% of cases by various investigators. The surgical retrieval and cryopreservation of sperm, especially in men with non-obstructive azoospermia, to some extent ensures the availability of sperm at the time of intracytoplasmic sperm injection. In addition, this strategy can avoid unnecessary ovarian stimulation in those patients intending to undergo in vitro fertilization-intracytoplasmic sperm injection with freshly retrieved testicular sperm when an absolute absence of sperm in the testis is identified. Several different methods for the cryopreservation of testicular and epididymal sperm are available. The choice of the container or carrier may be an important consideration and should take into account the number or concentration of the sperm in the final preparation. When the number of sperm in a testicular biopsy sample is extremely low (e.g., 1-20 total sperm available), the use of an evacuated zona pellucida to store the cryopreserved sperm has been shown to be an effective approach.